Berita Polemik 4 Pulau Aceh dalam Bingkai Media Online Republika.co.id dan Mediaindonesia.com - Siregar, Rachmi Kurnia; Kurniansyah, Rafli Akram; Fadhlurahman, Hanif (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The emergence of the decree of the Ministry of Home Affairs reviewing 4 Aceh Islands namely Panjang Island, Lipan Island, Mangkir Gadang Island, and Mangkir Ketek Island which will be transferred to the territory of North Sumatra Province (Sumut) sparked public reaction. This government decision brought a new polemic between Aceh Province led by Governor Muzakir Manaf (Mualem) and North Sumatra Governor Bobby Nasution. The two provinces are in tension regarding who has the right to ownership of the 4 islands. This polemic has attracted attention in the mass media, especially for online media including Republika.co.id and Mediaindonesia.com. The news analyzed was in the edition of June 13 - June 17, 2025. This study uses a qualitative approach using Robert N Entman’s framing analysis model in dissecting the research. Researchers selected 4 news stories in each media as research objects. The results of the study show that there are differences in news framing between Republika.co.id and Mediaindonesia.com. Republika.co.id, in its reporting, tends to side with the Acehnese people as the aggrieved party by presenting information regarding the demands of students and religious leaders. Meanwhile, Mediaindonesia.com tends to side with the central government as the authority in resolving the Aceh 4 Islands controversy. This tendency is evident in Mediaindonesia.com’s selection of sources, which cite statements from Coordinating Minister Yusril, Deputy Minister of Home Affairs Bima Arya, Chairman of Commission II of the Indonesian House of Representatives, and President Prabowo as a representative of the central government.